The effectiveness of employer branding on social media platforms of today: avenues for enhancing recruitment at Wonderif Studio - Hassan, Abidur Rafi (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.